Seasonal Activity of the Pomegranate Fruit Moth Ectomyelois ceratoniae Zeller and its Possible Integrated Control in Ain al-Tamr, Karbala Governorate, Iraq - Ibrahim, Hussein K.; Mohammed, Akram A. (Department of Agronomy and Horticulture, IPB University, 2025)
The pomegranate fruit moth, E. ceratoniae Zeller, is a significant pest of pomegranate worldwide. Seasonal monitoring and integrated control trials were carried out in pomegranate orchards of Ain al-Tamr, Karbala Governorate (Iraq) during the 2024 growing season (15 May–15 September 2024). Regular adult male f light began in early May and continued until mid September, peaking in mid-August (35.15 male moth per trap) at a mean ambient temperature of 35.85°C and a relative humidity of 20.47%. Field trials evaluated botanical oils (thyme and juniper, 7% v/v), the entomopathogenic fungus Beauveria bassiana (commercial formulation), their combinations, and the insecticide imidacloprid (Imidor 200 SL) under a randomized complete block design. Treatments and monitoring (pheromone traps) were repeated following two sprays (7 June and 7 July 2025). Combined B. bassiana + 7% thyme oil provided control comparable to Imidor, reducing fruit infection to 3.3% and trap captures to 1 male per trap, whereas B. bassiana alone reduced infection to 10% and trap captures to five males per trap. Overall, treated plots averaged 13.31% infection, compared to 55% in controls, after the second spray. Statistical analyses (ANOVA, post hoc tests) confirmed significant treatment effects. These findings indicate that integrating B. bassiana with botanical oils can effectively reduce E. ceratoniae infestation and may serve as a sustainable alternative to routine chemical control in Ain al-Tamr pomegranate orchards.